Benzodiazepine dependence – the conditionsof severe course. Case report - Perzyński, Adam; Kłębukowska, Ida; Chmiel-Perzyńska, Iwona; Olajossy, Marcin (Current Problems of Psychiatry, 2015)
Benzodiazepines (BDAs), synthetized for the first time by Leon Sternbach, have been in use since the early sixties and are currently appropriable in many branches of medicine. Acting on the inhibitory receptor of gamma aminobutyric acid (GABA) they enhance the influx of chloride ions into the cell, resulting in hyperpolarization of the cell membrane. By interfering with the different types of GABAergic receptors, BDAs induce various effects: anxiolytic, myorelaxant, hypnotic, anticonvulsant, sedative. Studies performed in North America and Europe on BDAs use show that it concerns 0.4-6% of general population, and their chronic use is significantly more frequent in people over 65 years of age, especially in the ones suffering from physical or mental disturbances. It is estimated that among BDA users, 26-76% take BDA chronically and 20-50% have withdrawal symptoms in case of discontinuation, even when small doses have been used. Withdrawal symptoms include anxiety, sleep and cognitive disturbances, muscle tremor, oversensitivity to stimuli, depersonalization, hallucinations, agitation and seizures. More intensive withdrawal symptoms are usually correlated with chronic use and high doses, and the drugs of short half life time.The paper describes the case of many years’ benzodiazepine dependence, patient’s drug gaining methods, the influence on the functioning and the course of the treatment with considering motivating factors.